2001
DOI: 10.1099/00207713-51-2-633
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the classical Mycoplasma lipophilum cluster (Weisburg et al. 1989) and description of two new clusters in the hominis group based on 16S rDNA sequences.

Abstract: The Mycoplasma lipophilum cluster (Weisburg et al. 1989) in the hominis group of the mollicutes is re-evaluated in this work to update the phylogenetic framework for classification of species within the genus Mycoplasma. Therefore, sequences of the 16S rRNA gene were determined from previously described species, and 11 were found to be closely related to the M. lipophilum cluster. A selection of members of the other hitherto defined clusters of the hominis group was included for phylogenetic analysis, revealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Two species, Mycoplasma columbinum and M. columbinasale, could not be distinguished, although previous studies have indicated that they are less than 97 % similar by 16S sequence analysis (Pettersson et al, 2001). Even when cultures were obtained from several different collections the two isolates gave identical profiles.…”
Section: Porcine Mycoplasma Speciesmentioning
confidence: 78%
See 1 more Smart Citation
“…Two species, Mycoplasma columbinum and M. columbinasale, could not be distinguished, although previous studies have indicated that they are less than 97 % similar by 16S sequence analysis (Pettersson et al, 2001). Even when cultures were obtained from several different collections the two isolates gave identical profiles.…”
Section: Porcine Mycoplasma Speciesmentioning
confidence: 78%
“…Similarly, the canine mycoplasma M. maculosum showed a high degree of similarity to the lion mycoplasma M. leopharyngis by 16S and 16S-23S IGS analysis and gave identical DGGE profiles. Previous studies have also highlighted the high degree of similarity in 16S sequence and identical biochemical characteristics of these species (Pettersson et al, 2001).…”
Section: Porcine Mycoplasma Speciesmentioning
confidence: 79%
“…These results show that various strains of Mycoplasma species do circulate in Turkish cattle herds. M bovis, M alkalescens and M canadiense all belong to the hominis group of mycoplasmas but belong to different clusters, the lipophilum ‐cluster for M bovis and the hominis‐cluster for M alkalescens and M canadense (Pettersson and others 2000, 2001). These three species are pathogenic for cattle and may induce mastitis or fertility disorders in adult cows, or arthritis in calves (Pfutzner and Sachse 1996, Booker and others 1999, Infante‐Martinez and others 1999, Bielanski and others 2000, Butler and others 2000, Hirose and others 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In mollicutes, such an element has not been thoroughly described except for the ICEF of the human-infecting Mycoplasma fermentans strain PG18, in which it occurs in two versions, ICEF-I (1 copy) and ICEF-II (3 copies), and produces a circular form after excision from its locus (6). This mycoplasma belongs to the hominis phylogenic group, along with Mycoplasma agalactiae and Mycoplasma bovis (15), which are ovine-caprine and bovine pathogens, respectively.…”
mentioning
confidence: 99%